Besnoitia tarandi in Canadian woodland caribou - Isolation, characterization and suitability for serological tests. - Schares, Gereon; Jutras, Charles; Bärwald, Andrea; Basso, Walter Ubaldo; Maksimov, Aline; Schares, Susann; Tuschy, Mareen; Conraths, Franz J; Brodeur, Vincent (International Journal for Parasitology: Parasites and Wildlife, 2019)
In the present study, we report the first isolation of from North America and the second of at all. The parasite was isolated directly from the skin of a Canadian woodland caribou from the migratory ecotype. The animal belonged to the Leaf River Herd, in Northern Quebec, Canada. The isolate was designated Bt-CA-Quebec1. Sequencing of the 3'-end of the 18S rRNA gene, the complete sequence of the ITS1 and the 5'-end of the 5.8S rRNA gene of Bt-CA-Quebec1 revealed only minor differences to rDNA gene fragments of . In contrast, the patterns for the microsatellite loci Bt-20 and Bt-21 varied substantially from those reported for and Surprisingly, the typing results in the loci Bt-6 and Bt-7 differed between Bt-CA-Quebec1 and results obtained for skin samples from caribou of the Canadian regions of Nunavut and the Northwest Territories reported by other investigators. This indicates that differences might exist among in caribou from different regions in Canada. Mice (γ-interferon knockout) intraperitoneally inoculated with 1.2 × 10 or 1.5 × 10 bradyzoites mechanically released from skin tissue cysts fell ill 8, 9 or 18 days post inoculation. GKO mice inoculated with 3.0 × 10 tachyzoites isolated from the peritoneal cavity of a bradyzoites-inoculated mouse became ill earlier, i.e. 5 days post inoculation. Lung was the predilection site in all mice. Bt-CA-Quebec1 tachyzoites rapidly grew in MARC-145 cells and were used for antigen production. Comparative Western blot analyses revealed only a few differences between Bt-CA-Quebec1 and Evora antigen when probed with sera collected from chronically infected caribou. Due to its fast growth , the Bt-CA-Quebec1 isolate may represent an interesting antigen source to establish -specific serological tools and to study the biology of this parasite species further.